High-resolution magnetic resonance imaging in isolated, traumatic oculomotor nerve palsy: A case report - Eisenhut, Felix; Gerner, Stefan; Gölitz, Philipp; Dörfler, Arnd; Seifert, Frank (Radiology Case Reports, 2021)
Traumatic, isolated oculomotor nerve palsy is a rare clinical finding and only few reports demonstrate associated magnetic resonance imaging (MRI) findings. Here, we present the case of a 70-year-old woman with left-sided oculomotor nerve palsy following a mild head trauma due to an e-bike accident. Post-traumatic cerebral computed tomography revealed punctiform hemorrhage in the left interpeduncular cistern and the following MRI confirmed an intraneural hemorrhage of the left oculomotor nerve. Nine weeks later, the follow-up MRI showed progressive atrophy and contrast-enhancement of the left oculomotor nerve. To support functional recovery, a treatment with intravenous corticosteroids was started. Six months later, the patient presented with improved oculomotor nerve function and partial recovery of ptosis and diplopia. In accordance, MRI demonstrated recurrent contrast-enhancement of the atrophic nerve. In conclusion, high-resolution MRI allows the reliable delineation of the oculomotor nerve and can support diagnosis in trauma patients with isolated oculomotor nerve palsy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Case report; Magnetic resonance imaging; Oculomotor nerve; Traumatic nerve palsy